Seeking signs of transparency: audit, materiality, and monuments to active citizenship in New Delhi. (27th September 2019) - Webb, Martin
Abstract: In New Delhi, the Chief Information Commissioner has ordered that municipal councillors should 'proactively disclose' details of the amounts spent on public works via Hindi‐language noticeboards displayed in every city ward. As 'appropriate' technology designed to reach out to the common people, the noticeboards are part of an ongoing technomoral project to develop and democratize citizen engagement with urban governance. An audit of the noticeboards carried out by Information Commission officials and 'right to information' activists reveals that many are badly positioned or assembled from inappropriate materials. As such, they are judged to be unreliable actants in the project to prefigure a more open and transparent city administration. A focus on the materiality and temporal orientation of the noticeboards, however, reveals them to be productive in other ways. We come to understand the noticeboards as monuments to earlier projects of active citizenship and as ongoing sites of contest or collaboration between actors concerned with their audit and remediation. Abstrait: À la recherche de signes de transparence : audit, matérialité et monuments célébrant la citoyenneté active à New Delhi Résumé À New Delhi, le président de la Commission à l'information a ordonné aux conseillers municipaux de « divulguer » de manière proactive le détail des sommes dépensées en travaux publics via des panneaux d'affichage en hindi dans chaque quartier. En tant que technologie « appropriée » et conçue pour toucher le grand public, ces panneaux d'affichage s'inscrivent dans un projet techno‐moral en cours visant à développer et à démocratiser la participation des citoyens à la gouvernance urbaine. Un audit des panneaux d'affichage, effectué par des fonctionnaires de la Commission de l'information et des activistes du « droit à l'information », révèle que nombre d'entre eux sont mal placés ou assemblés à partir de matériaux inappropriés. En tant que tels, ils sont jugés peu fiables en ce qui concerne la préfiguration d'une administration urbaine plus ouverte et transparente. Mais si l'on met l'accent sur la matérialité et l'orientation temporelle des panneaux d'affichage, ceux‐ci se révèlent productifs d'une autre manière. Ils peuvent être compris comme des monuments célébrant d'anciens projets de citoyenneté active, ainsi que comme des enjeux durables de la compétition ou de la collaboration entre les acteurs concernés par leur audit et leur restauration.